2002
DOI: 10.1175/1520-0493(2002)130<0700:kcoamy>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Characteristics of a Mei-yu Front Detected by the QuikSCAT Oceanic Winds

Abstract: Based on conventional surface observations and NASA Quick Scatterometer (QuikSCAT) data, a heavy rainfall event that occurred in the Taiwan mei-yu season was chosen to further study the kinematic characteristics of the accompanying surface front. With the help of the QuikSCAT oceanic surface winds, it was found that the location and propagation of a mei-yu front over the ocean to the east of Taiwan during 10-12 June 2000 are better represented by the frontal wind shift line, which was located approximately on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…4b). In a study of the kinematic characteristics of a Mei-yu front, Yeh et al (2002) demonstrated the usefulness of high-resolution (25 km) oceanic surface wind data, derived from the NASA Quick Scatterometer (QuikSCAT) satellite, which was launched in June 1999. Unfortunately, there was no such kind of data available for validating the location of the windshift line during the TAMEX in 1987.…”
Section: Numerical Results From the Control Experiments A Evolution Omentioning
confidence: 99%
See 2 more Smart Citations
“…4b). In a study of the kinematic characteristics of a Mei-yu front, Yeh et al (2002) demonstrated the usefulness of high-resolution (25 km) oceanic surface wind data, derived from the NASA Quick Scatterometer (QuikSCAT) satellite, which was launched in June 1999. Unfortunately, there was no such kind of data available for validating the location of the windshift line during the TAMEX in 1987.…”
Section: Numerical Results From the Control Experiments A Evolution Omentioning
confidence: 99%
“…Satellite pictures usually show a synoptic-scale stratiform cloud band along the front with organized mesoscale convective systems embedded within the band. Past observational and numerical studies of the kinematic structure of the Mei-yu front revealed very complicated flow patterns due to the influence of organized convective systems (Lin et al 1992;Hsu and Sun 1994;Yeh et al 2002;Sun et al 1995, and others). Once in a while, a dry Mei-yu front without any convective system does occur.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mei-Yu rainfalls are produced by surface frontal systems which advance southeastward from southern China to Taiwan from mid to late spring through early to mid summer each year. The fronts are usually accompanied by a synoptic-scale cloud band with embedded mesoscale convective systems (MCSs), extending several thousand kilometres from southern Japan to southern China with an approximately east-west orientation (Yeh et al, 2002). During the passage of a Mei-Yu frontal system, a few very active mesoscale convective cells may develop repeatedly, causing heavy and localized rainfall for the area.…”
Section: Spatial Variation Of Hourly Rainfallmentioning
confidence: 99%
“…Only when decreasing the resolution of the Goddard Earth Observing System general circulation model (GCM) to 0.5°ϫ 0.5°do Conaty et al (2001Conaty et al ( , p.1854 produce frontal features that are "reminiscent of those seen in high-resolution scatterometer wind data." Scatterometer data have been used to study the development of storms in the Southern Hemisphere (Levy and Brown 1991;Levy 1989McMurdie and Katsaros 1991;Yuan et al 1999;Milliff et al 1999;Hilburn et al 2003) and fronts or frontogenesis (Zierden et al 2000;Yeh et al 2002) but not to study frontal instabilities. The goal of this study is to apply an attribution technique to scatterometer data to analyze the development of three fronts over the Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%